Pengembangan Masyarakat Islam Berwawasan Ekoteologi - Mokh. Ulil Hidayat (Jurusan Pengembangan Masyarakat Islam Fakultas Dakwah dan Komunikasi Islam, UIN Datokarama Palu., 2025)
This article discusses the concept of Islamic community development with an ecotheological perspective, which is a theological approach that views the relationship between humans and nature as an integral part of servitude to Allah SWT. In Islam, the universe (al-‘ālamīn) is a sign of Allah's power (āyāt Allāh) that must be preserved and maintained. Currently, ecological damage is a sign of a spiritual and moral crisis. Therefore, a community development model based on values that reflect faith, trust, and ecological responsibility is needed. This study uses qualitative (library research) with a reflective theological-normative approach with qualitative analysis of primary Islamic sources, the Qur'an and Hadith, as well as contemporary literature. The results of the study show that the development of an ecotheology-oriented Islamic society can be achieved through the transformation of religious consciousness: ecotheology education and literacy, ecotheology cultural movements, green economy, and synergizing spiritual values in public policy.